The Model of Indirect Pricing Transactions and the New Boundaries of the Sharing Economy - Ge JunGuo；Yukuan (Contemporary Social Sciences, 2021)
In recent years, the sharing economy has become more prevalent in many lives. While bringing convenience to the public, it has also improved resource efficiency, thus gradually driving economic development. By studying indirect pricing transactions, the authors have discovered a new sort of sharing economics which may be able to resolve the issue presented by intangible assets (such as entrepreneurship) and provide new ideas for addressing social problems. Compared with the traditional sharing economy, this new economic pattern has wider potential utility. The authors hold that their indirect pricing theory establishes the theoretical foundation of new sharing economics, while the model of indirect-pricing transaction extends the boundaries for the existing sharing economy.